2003
DOI: 10.2514/2.6147
|View full text |Cite
|
Sign up to set email alerts
|

Ignition Delay for Jet Propellant 10/Air and Jet Propellant 10/High-Energy Density Fuel/Air Mixtures

Abstract: Jet propellant 10 [(JP-10) or exotetrahydrodicyclopentadiene]is one of the leading candidate fuels for use in pulse detonation engine applications.As such, its ignition delay characteristics have been studied previously in very dilute mixtures at pressures from 1 to 9 atm and temperatures from 1300 to 1670 K. The ignition delay times are studied of JP-10/air and JP-10 blended with methylated PCU alkene dimer, nitronorbornane, dinitronorbornane, and ethylhexyl nitrate in air at pressures from 10 to 25 atm and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…The Davidson and Mikolaitis datasets used the peak CH ⁄ emission as the indicator of ignition, while both Colket and Wang experiments used initial rise onsets of the CH ⁄ emission, leading to faster measured ignition times. Mikolaitis and coworkers [9] found that at intermediate temperatures, two emission peaks for ignition delay were present. The first peak ignition delays from the CH emission were recommended by the authors the true indicator of ignition and are compared with the model predictions here.…”
Section: Ignition Delaysmentioning
confidence: 98%
See 3 more Smart Citations
“…The Davidson and Mikolaitis datasets used the peak CH ⁄ emission as the indicator of ignition, while both Colket and Wang experiments used initial rise onsets of the CH ⁄ emission, leading to faster measured ignition times. Mikolaitis and coworkers [9] found that at intermediate temperatures, two emission peaks for ignition delay were present. The first peak ignition delays from the CH emission were recommended by the authors the true indicator of ignition and are compared with the model predictions here.…”
Section: Ignition Delaysmentioning
confidence: 98%
“…Temperature range (K) Pressure range (atm) Equivalence ratios (U) Bath gas Ignition delay metric Colket and Spadaccini [8] 1250-1500 3-7 0.5-1.5 Ar Initial rise onset in OH ⁄ emission Davidson et al [7] 1300-1700 1-6 0.5-2.0 Ar Peak CH ⁄ emission Mikolaitis et al [9] 1200-2000 10-25 1.0 N 2 Peak CH ⁄ emission Wang et al [10] 1000-2100 1.5-5. [41] and found that the OH concentration is primarily sensitive to C 2 oxidation reactions.…”
Section: Datasetmentioning
confidence: 98%
See 2 more Smart Citations
“…Although studies [1][2][3][4][5][6][7][8][9][10][11] have been conducted to investigate the physical properties and catalytic cracking of JP-10 at various temperatures and pressures by means of spectroscopic, gas chromatographic, and mass spectrometric analyses, the high-temperature thermal decomposition chemistry of JP-10 is still not well understood.…”
Section: Introductionmentioning
confidence: 99%